NEEDS ANALYSIS AND ENGLISH FOR LEGAL PURPOSES COURSE DEVELOPMENT: A CASE STUDY ON AN ELP SYLLABUS DESIGN FOR UNIVERSITY STUDENTS - BRETAN, Bianca Doris (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Needs analysis and English for Legal Purposes Course Development: A Case Study on an ELP Syllabus Design for University Students. The present paper investigates the connection between students’ learning needs as reflected in the initial needs analysis and ELP syllabus design. Initiated at the beginning of the academic year the study investigates solutions to bridge the gap between the linguistic and professional needs of students attending legal English classes and their course syllabus. A typical challenge for the students’ instructor is the fact that they have little, typically no prior experience with the profession for which they hope to qualify during their studies. The fact that compulsory language courses are often placed in the students’ first year of bachelor study programmes makes the intention to offer relevant course content even more difficult. The structure of the article is the following: first is given a scope for the study, then needs analysis is presented in relation to teaching ESP for the general public and university students; finally, the findings are interpreted in the context of changes in teaching strategies and course design. The article concludes by pointing out that taking into consideration students’ expectations and needs is strongly correlated with the quality and the relevance of the course. REZUMAT. O analiză a corelării nevoilor de învăţare cu conţinutul cursului: studiu de caz-elaborarea unui syllabus de limbaj juridic în limba engleză pentru studenţi. Articolul de faţă analizează legătura dintre nevoile de învăţare ale studenţilor aşa cum sunt ele reflectate în analiza de nevoi iniţială şi crearea unui syllabus de curs pentru limbaj juridic. Început la debutul anului universitar, studiul investighează soluţii pentru micşorarea decalajului dintre nevoile lingvistice şi profesionale ale studenţilor care participă la cursul de limbaj juridic de specialitate şi syllabusul de curs. Una din încercările la care e supus profesorul într-o asemenea situaţie este faptul că, în general, studenţii primului an au o părere foarte vagă despre cunoştinţele pe care ar trebui să le posede în limbajul de specialitate referitor la profesia pe care o vor îmbrăţişa. Structura articolului este următoarea: se prezintă scopul studiului, apoi se discută relaţia dintre analiza nevoilor de învăţare şi predarea limbajelor de specialitate publicului larg şi studenţilor; în cele din urmă sunt interpretate rezultatele în contextul schimbărilor pe care acestea le aduc în ceea ce priveşte strategia de predare şi conceperea cursului. Concluzia articolului este că luarea în considerare a dezideratelor şi nevoilor studenţilor este în strânsă legătură cu calitatea şi relevanţa cursului. Cuvinte-cheie: ESP, ELP, predarea şi învăţarea limbilor străine, analiza nevoilor de învăţare, creare de curs, nevoi profesionale, studenţi la Drept, educaţie universitară.